Design of a Wilkinson Power Divider with harmonic suppression for mobile application - Iskandar Tuah, Hanis Humaira; Alam, A. H. M. Zahirul (AlamBiblio Publishers, 2024)
his paper presents a Wilkinson Power Divider (WPD) operating at 6 GHz capable of suppressing unwanted harmonics up to the 3rd harmonic. The design formulas are analysed and presented in detail. Power dividers are widely used in microwave circuit structures. Indeed, this paper outlines the design and simulation of a 1:1 power divider for mobile applications using CST Studio Suite.